Exploring the Key Factors Affecting Development of Bond Market in Bangladesh: An Application of Exploratory Factor Analysis (EFA) - Begum, Noor Nahar; Kamal, Md Aktar (International Journal of Economics and Financial Issues, 2018)
An efficient and well-functioning government bond market is often considered important to the smooth functioning of financial markets more generally. To enhance corporate bond financing, it is important to examine factors that affect the effective development of bond markets in Bangladesh. The aim of this study was to determine key factors affecting the development of bond market in Bangladesh. The study was conducted over 60 respondents from financial institutions by using convenient sampling technique. For data collection structured questionnaire has been used. The questionnaire was developed with 5-point Liker scale where, 1 refers to ‘strongly disagree’ and 5 refers to ‘strongly agree. The study attempts to identify the determinants of bond market development in Bangladesh economies through examining the relationship of bond issuance with selected key financial and economic factors. Major determinants for bond market development in Bangladesh include developing the money market, strengthening the government’s debt and cash management capacity, reforming the national savings scheme, reducing issuance costs for corporate bonds, broadening the investor base, increasing transparency in the secondary market, creating and enabling legal and regulatory framework, strengthening the credit rating industry. Keywords: Bond Market; Factor Analysis; Capital Market. JEL Classifications: G1, G2, G4